2021
DOI: 10.1038/s41398-021-01690-3
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of AMPA receptor GluA1 subunit gene (Gria1) causes circadian rhythm disruption and aberrant responses to environmental cues

Abstract: Dysfunction of the glutamate α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor GluA1 subunit and deficits in synaptic plasticity are implicated in schizophrenia and sleep and circadian rhythm disruption. To investigate the role of GluA1 in circadian and sleep behaviour, we used wheel-running, passive-infrared, and video-based home-cage activity monitoring to assess daily rest–activity profiles of GluA1-knockout mice (Gria1−/−). We showed that these mice displayed various circadian abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 124 publications
(162 reference statements)
2
11
0
Order By: Relevance
“…We have previously detected relevant levels of wheel running activity in young female and male wild-type mice from prepubescent age onward (Reiber et al, 2022). Considering wheel running in GluA1 deficient mice, there exist two studies analyzing the performance of adult Gria1 −/− mice (Maksimovic et al, 2014;Ang et al, 2021). In line with our findings in adolescent Gria1 −/− mice, Maksimovic et al (2014) found no significant genotype-related difference during adulthood considering the distance run in the wheel.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We have previously detected relevant levels of wheel running activity in young female and male wild-type mice from prepubescent age onward (Reiber et al, 2022). Considering wheel running in GluA1 deficient mice, there exist two studies analyzing the performance of adult Gria1 −/− mice (Maksimovic et al, 2014;Ang et al, 2021). In line with our findings in adolescent Gria1 −/− mice, Maksimovic et al (2014) found no significant genotype-related difference during adulthood considering the distance run in the wheel.…”
Section: Discussionsupporting
confidence: 83%
“…Considering bench-top assessment, GluA1 deficient adult mice have been observed to show normal locomotor activity during continuous light/dark phase monitoring (Fitzgerald et al, 2010;Procaccini et al, 2011). However, as recently reported by Ang et al (2021), Gria1 −/− mice displayed significantly reduced locomotor activity in the dark phase and increased locomotor activity in the light phase as compared to the wild-type control group, indicating relevant circadian rhythm abnormalities related to the genetic deficiency. Thus, although hyperlocomotion and increased resting durations in the zone 'feeding' observed in adolescent Gria1 −/− mice may be linked to lower post-weaning body weights, the activity levels measured are likely to be biased due to the selected short observation interval.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…All models have been shown to induce defined syndromes in mice, leading to alterations in the animals’ emotional or cognitive behaviors. GluA1 knockout mice represent a well-known animal model for depression based on mutation of the AMPA receptor subunit 1 ( Zamanillo et al, 1999 ; Bannerman et al, 2004 ; Chourbaji et al, 2008 ; Wiedholz et al, 2008 ; Sanderson et al, 2009 , 2017 ; Fitzgerald et al, 2010 ; Inta et al, 2010 ; Bygrave et al, 2016 , 2019 ; Eltokhi et al, 2020 ; Ang et al, 2021 ), which is consistent with the glutamate hypothesis of depression ( Sanacora et al, 2012 ). As stress-based models, we used the daily experience of restraint stress on the one hand and on the other, chronic pharmacological treatment with the stress hormone corticosterone ( Moda-Sava et al, 2019 ).…”
Section: Introductionmentioning
confidence: 62%
“…The loss of GluA1 leads to an increase in depression-associated learned helplessness ( Chourbaji et al, 2008 ), hyperlocomotion in the open field ( Wiedholz et al, 2008 ), novelty- and stress-induced locomotor hyperactivity, altered coping in the forced swim test and in approach-avoidance conflict tests ( Fitzgerald et al, 2010 ), cognitive impairments in short-term memory, puzzle-solving and attention ( Zamanillo et al, 1999 ; Bannerman et al, 2004 ; Sanderson et al, 2009 ; Ben Abdallah et al, 2011 ; Austen et al, 2021 ; Strickland et al, 2021 ). In addition, they show circadian disturbances, striking rest-activity pattern changes, and even reduced voluntary running ( Ang et al, 2021 ), another valuable home cage-based parameter for well-being ( Mallien et al, 2020 ; Weegh et al, 2020 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%